2018
DOI: 10.1016/s2215-0366(18)30051-8
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events and maltreatment in conversion (functional neurological) disorder: systematic review and meta-analysis of case-control studies

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
227
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 324 publications
(250 citation statements)
references
References 62 publications
15
227
3
5
Order By: Relevance
“…Contemporary explanations have moved away from psychodynamic trauma-focused models and instead emphasise dysfunction of higher-order cognitive processes 7–9. Nevertheless, the importance of psychosocial adversity in FND cannot be underestimated given that rates of early-life and proximal adverse events have been repeatedly found to be higher in FND samples relative to controls 10. Stressful life-events including abuse/neglect, ongoing relationship disturbances, occupational stress and caring responsibilities are commonly reported 6 11–13…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary explanations have moved away from psychodynamic trauma-focused models and instead emphasise dysfunction of higher-order cognitive processes 7–9. Nevertheless, the importance of psychosocial adversity in FND cannot be underestimated given that rates of early-life and proximal adverse events have been repeatedly found to be higher in FND samples relative to controls 10. Stressful life-events including abuse/neglect, ongoing relationship disturbances, occupational stress and caring responsibilities are commonly reported 6 11–13…”
Section: Introductionmentioning
confidence: 99%
“…A recent review found that stressful life events were significantly more common in people with FMDs and may be relevant to the aetiology of the condition for some patients. 7 Despite the similarities outlined above, there are differences between these two cases. The progression of their FTs were highly different: the patient in case 1 has had deterioration in his symptoms over time, yet in case 2 there was steady improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of case-control studies found higher frequency of both childhood and adulthood stressors in people with FND than controls 1. It reported OR=2.8–4.3 for stressful life events preceding FND symptom onset, with higher ratios in studies using better-quality interview methods.…”
Section: Stress and Healthmentioning
confidence: 99%
“…Growing research focus on sensitive periods of brain development at which maltreatment may exert greater harm, predisposing to psychopathology,9 will inform our understanding of how traumatic stressors interact with biological susceptibility in FND. However, the quality of research which recognises the key role played by stress, is often limited by methodological issues such as self-report questionnaires and recall bias 1. Detailed interview techniques, which blind-rate a range of experiences, contextualised to the person’s life, remain the gold standard, but require considerable time and training, and cannot fully objectify (at least partially) subjective stress experiences.…”
Section: Implications For Fndmentioning
confidence: 99%